Unlocking Prerogative Writs: Concept and Scope of Writ Jurisdiction under Article 199 of the Constitution of Pakistan - Khan, Yasir Rashid; Bashir, Aiman (Law and Policy Review, 2022)
The concept of ‘prerogative writs’ is as old as common law itself. Historically, public law remedies have been granted in the name of the Crown. There are five different kinds of writs or orders, which include prohibition, mandamus, certiorari, quo warranto, and habeas corpus. Undoubtedly, writ jurisdiction is an indispensable weapon with the judiciary to check the constitutional legality of the actions and inactions of the executive arm of the government. This paper aims to provide a general account of the origin, concept, types, scope, and nature of prerogative writs in light of the principles established through case laws. It concludes that the framers of the constitution have conferred an extraordinary jurisdiction on High Court(s) under Article 199 for the enforcement of fundamental rights guaranteed under the constitution of the Islamic Republic of Pakistan, 1973.